From buzz to bust: How fake news shapes the business cycle - Tiziana Assenza; Fabrice Collard; Patrick Fève; Stefanie J. Huber (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
The proliferation of fake news poses significant challenges for policymakers and raises concerns about its potential impact on economic stability. This paper explores this question, focusing on the macroeconomic effects of technology related fake news in the US for the period 2007-2022. Utilizing a novel dataset of fact-checked statements from PolitiFact, we construct a binary indicator to build a proxy for the exogenous variation in fake news issuance. Adopting a proxy-VAR approach, we show that technology fake news increases macroeconomic uncertainty, exacerbates unemployment, and depresses industrial production. Similar effects are observed for fake news related to the supply side, such as tax rates or the price of gas. On the contrary, fake news related to government finance, market regulation, or the labor market does not impact economic stability. Furthermore, fake news that conveys negative information about technological developments exhibits stronger depressive impacts than positive ones.
Keywords: C32; E32; 330; Fake news; business cycle; proxy-VAR